Coastal resources - Awange, Joseph (2018)
© Springer International Publishing AG 2018. The extreme importance of coastal zones for countries with highly-populated coastal areas has been discussed in Goncalves and Awange, J Surv Eng, 2007, [2] who highlight the concerns about their future, particularly on the state of their natural resources that provide life support and opportunities for economic development and tourism for these countries (Clarck, JR, Integrated management of coastal zones, 1992, [3] ). However, one of the main environmental problems facing coastal areas the world over is that of coastal erosion, which includes, e.g., beach erosion and other natural and anthropogenic environmental factors that are present along the shoreline.